MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA DENGAN MENGGUNAKAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION - Melany Tri Ananda; Atri Waldi; Arwin; Reinita (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This research aims to describe the improvement in Pancasila education learning outcomes using an active learning model with the role reversal question type in class V students at SDN 18 Kampung Baru, Padang City. This type of research is classroom action research. The research subjects were 21 students in class V of SD N 18 Kampung Baru, Padang City. The data collection method in this research uses tests, observation and documentation. The research instruments are tests and observation sheets. The data analysis technique used is descriptive qualitative. The indicator of the success of the action is marked by ?80% of the total number of students who took part in the learning process having obtained a score of ?86.27. The results of the research showed that there was an increase in Pancasila education learning outcomes for fifth grade students at SD N 18 Kampung Baru, Padang city after using the active learning model with the role reversal question type in both cycle I and cycle II. 1.) in the results of the implementation of learning in cycle I, the average planning value was 87.45%, then increased in cycle II, namely 95.8%. 2.) In cycle I, teacher activity averaged 91%, increasing in cycle II to 96.4%. 3.) In carrying out student activities, the average was 91%, increasing in cycle II to 96.4%.